PENATALAKSANAAN FISIOTERAPI PADA FROZEN SHOULDER DEXTRA DENGAN TRANSCUTANEUS ELECTRICAL NERVE STIMULATION, INFRA RED DAN FREE ACTIVE EXERCISE - Wardani, Shinta Oktavia Kusuma; Kuswardani, Kuswardani (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Title of Final Study Report : Physiotherapy Management of Frozen Shoulder Dextra with Transcutaneal Electrical Nerve Stimulation, Infra Red, and Free Active Exercise Background : Frozen Shoulder is a condition where the shoulder becomes inflamed so that the connective tissue around the shoulder joint becomes tight and thick. This causes pain and movement restrictions due to the scope of myofascial disorders with reduced or limited mobility capsular patterns. The modalities given for frozen shoulder are Transcutaneous Electrical Nerve Stimulation, Infra Red and Free Active Exercise. Methods : This scientific paper is a case study, highlighting patient cases and collecting data through the Physiotherapy process. The modalities provided are Transcutaneous Electrical Nerve Stimulation, Infra Red and Free Active Exercise. Results : After receiving physiotherapy treatment 4 times, we found Scope of Joint Movement (LGS) of the shoulder dextra, a decrease in pain in the shoulder dextra, an increase in the strength of the moving muscles in the shoulder dextra and an increase in the patient's functional activity ability using the Shoulder Pain and Disability Index (SPADI). Conclusion : Management, Transcutaneous Electrical Nerve Stimulation, Infra Red and Free Active Exercise have been proven to eliminate spasms, increase joint Range of Motion (ROM), reduce pain, increase muscle strength and increase functional activity abilities using the Shoulder Pain and Disability Index (SPADI).